165k views
2 votes
Simplify the expression.
9(4+t) - 7(t + 3)
9(4 +t) - 7(t + 3) =

User Zawarudo
by
5.3k points

1 Answer

3 votes

Answer:

−63t2−439t−741

Explanation:

Let's simplify step-by-step.

9(4+t)−7(t+3)(9)(4+t)−7(t+3)

Distribute:

=(9)(4)+(9)(t)+−63t2+−441t+−756+(−7)(t)+(−7)(3)

=36+9t+−63t2+−441t+−756+−7t+−21

Combine Like Terms:

=36+9t+−63t2+−441t+−756+−7t+−21

=(−63t2)+(9t+−441t+−7t)+(36+−756+−21)

=−63t2+−439t+−741

User CoryDorning
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.